Implementation of Islamic Education in Early Childhood in Forming Religious Character at Raudhatul Athfal (RA) Islamic Boarding School Luhur - Oktrigana Wirian; Qaulan Raniyah; Tenang Tarigan; Naila Zahra Aprilia (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the implementation of Islamic education in early childhood in shaping religious character at RA Pesantren Luhur. The background of this research is based on the importance of instilling Islamic values from an early age as the main foundation for character development in children. This study employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation involving the principal, teachers, and students. The results of the study indicate that the implementation of Islamic education at RA Pesantren Luhur is carried out through various activities, such as daily religious habituation (praying, congregational prayer, and reciting the Qur’an), exemplary behavior demonstrated by teachers, and the use of engaging learning methods appropriate to children's developmental stages. The religious values instilled include faith, good morals, discipline, and responsibility. In addition, the role of teachers and the school environment is highly significant in shaping children's religious character. In conclusion, the implementation of Islamic education that is conducted consistently, systematically, and based on role modeling is effective in shaping the religious character of early childhood. Therefore, collaboration between schools and parents is essential to support the success of Islamic education from an early age.